2021
DOI: 10.1017/s1479262121000526
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of white Guinea yam (Dioscorea rotundataPoir.) cultivars from Benin as revealed by agro-morphological traits and SNP markers

Abstract: White Guinea yam (Dioscorea rotundata Poir.) is indigenous to West Africa, a region that harbours the crop's tremendous landrace diversity. The knowledge and understanding of local cultivars’ genetic diversity are essential for properly managing genetic resources, conservation, sustainable use and their improvement through breeding. This study aimed to dissect phenotypic and molecular diversity of white yam cultivars from Benin using agro-morphological and single nucleotide polymorphism (SNP) markers. Eighty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 55 publications
1
33
2
Order By: Relevance
“…These traits, including tuber yield, number of tubers per plant, tuber size, plant vigour, tuber hardness, YAD severity, dry matter content, and tuber oxidation could be utilized in evaluating genetic diversity among related Dioscorea spp. Agre et al [12,38,40] has reported the significant contribution of these traits in discriminating yam accessions.…”
Section: Genetic Parameters and Broad-sense Heritability Of Assessed ...mentioning
confidence: 99%
See 3 more Smart Citations
“…These traits, including tuber yield, number of tubers per plant, tuber size, plant vigour, tuber hardness, YAD severity, dry matter content, and tuber oxidation could be utilized in evaluating genetic diversity among related Dioscorea spp. Agre et al [12,38,40] has reported the significant contribution of these traits in discriminating yam accessions.…”
Section: Genetic Parameters and Broad-sense Heritability Of Assessed ...mentioning
confidence: 99%
“…Along with D. cayenensis and D. alata, they represent more than 95% of produced yam worldwide [1,11]. Farmers and consumers' preferences for a white Guinea yam variety depends on some key traits such as high tuber yield potential, low tuber flesh oxidation/browning, reduced tuber flesh hardening, high dry matter content, and tolerance to YMV and YAD [12]. Accordingly, the genetic improvement of this yam species will have a tremendous impact on food security and poverty alleviation if varieties combining those traits are developed and distributed to the predominantly resource-poor farmers of West Africa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the conservation of natural reserves, such as forests and savannah, and sustainable management of yam genetic resources, there is a need to provide farmers with improved varieties from diverse genetic backgrounds that combine high yields with pest and disease resistance and acceptable tuber quality [17]. Such an approach requires a thorough understanding of the genetic diversity within the existing germplasm for the effective selection of parental clones for hybridization [18].…”
Section: Introductionmentioning
confidence: 99%